Olfactory projection neuron rewiring in the brain of an ecological specialist - Benedikt R. Dürr; Enrico Bertolini; Suguru Takagi; Justine Pascual; Liliane Abuin; Giovanna Lucarelli; Richard Benton; Thomas O. Auer (Cell Reports)
Summary: Animal behaviors can differ greatly between closely related species. These behavioral changes are frequently linked to sensory system modifications, but central brain cell-type alterations might also be involved. Here, we develop advanced genetic tools to compare homologous central neurons in Drosophila sechellia, an ecological specialist, with the generalist Drosophila melanogaster. Through systematic morphological analysis of olfactory projection neurons (PNs), we reveal that the global anatomy of these second-order neurons is conserved. However, high-resolution, quantitative comparisons identify a striking case of convergent rewiring of PNs in two olfactory pathways critical for D. sechellia’s host location. Calcium imaging and labeling of pre-synaptic sites in these evolved D. sechellia PNs indicate that species-specific connections with third-order partners are formed. This work demonstrates that peripheral sensory evolution is accompanied by selective wiring changes in the central brain to facilitate ecological specialization and paves the way to compare other cell types throughout the nervous system.